‘The Devil’s Company’: A Grounded Theory Study on Aging, Loneliness and Social Change Among ‘Older Adult Children’ in Rural Indonesia - Schröders, Julia; Nichter, Mark; San Sebastian, Miguel; Nilsson, Maria; Dewi, Fatwa Sari Tetra (Frontiers in Sociology, 2021)
Introduction: As a consequence of rising life expectancies, many families are no longer made up of one, but two simultaneously aging generations. This elderly parent - older adult child (OAC) dyad has emerged as a newly overserved yet little explored demographic phenomenon. Studies on this intergenerational aging dyad and the possible ramifications of when caregivers are simultaneously aging with care-receivers are scarce, especially in low- and middle-income countries. This study explored the process by which rural Indonesian OACs experience their own aging, thereby gaining insights into how these newly evolving realities impact traditional ways of old-age care provision. Methods: This study has a qualitative design and draws on eight focus group discussions with 48 community-dwelling OACs (23 men, 25 women; mean age 64 years) in four rural villages in the Yogyakarta Special Region, Indonesia. The theoretical framework was largely inspired by symbolic interactionism aided by the sensitizing concepts of social network deficits, interpersonal emotions, and the social construction of risks. Data were analyzed using Grounded Theory as outlined by Corbin and Strauss. Results: Respondents’ accounts reflected four categories: (i) aging in a welt of chronic insecurity; (ii) OACs: a generation ‘betwixt and between’ expected demands and unmet expectations; (iii) landscapes of loneliness; and (iv) compromising against conventions. As depicted in a conceptual model, these categories interrelated with each other and were linked by a core category, “bargaining for a sense of security”, which collectively summarized a process by which OACs’ experienced their own course of aging. Conclusion: Our study provided insights into how and why loneliness emerged amidst the challenges of social and demographic transformations and how in response to this unconventional compromises were made, which affect both the networks of caretakers and the places of old-age care. It is doing so by including the perspectives of rural Indonesian OACs. The results showed how multiple intersecting negative experiences constrained the aging experiences of OACs and produced precarious aging trajectories. Our findings highlight the importance of old-age loneliness as an emerging public health and social problem by discussing how intrinsically this emotion was interwoven with social life.